Development of low cost “GloveMAP” based on fingertip bending tracking techniques for virtual interaction - Nazrul Hamizi, Adnan; Wan Khairunizam, Wan Ahmad; Shahriman, Abu Bakar, Dr.; M. Hazwan, Ali; Mohd Nasir, Ayob; Mohd Azri, Abd Aziz (IJENS Publishers, 2012)
Link to publisher's homepage at http://www.ijens.org/